(untitled) (Olhar de Professor, 2022)
This article aims to report the work developed in History classes, in 8th grade classes, at an elementary school in Porto Alegre’s city, which consisted in a cinema cycle’s creation, as an instrument for teaching and including Women’s History in the programmatic content of that year. In order to give visibility to women and using the concept of social representation to analyze the films, we sought to decompose and interpret the cinematographic works and then verify how women were represented through cinema. Through this pedagogical practice, it was possible to create a space for dialogue and exercise of empathy for conflict resolution, the understanding of our gender inequality and the empowerment of girls, as it gave visibility to women as historical subjects.